“FLIPPED CLASSROOM” FOR ORGANIZATION OF EFL STUDENTS’ INDEPENDENT WORK - E. V. Vulfovich (Высшее образование в России)
The article considers integrating flip teaching into language learning. The purpose of this study is to generalize the practical experience on using flip teaching at a non-linguistic university. To evaluate the effectiveness of “flipped classroom” model the following criteria have been adopted: students’ time spent on homework, students’ time spent on speech activity in class, the number of hours spent on studying the topic. The analysis of the data indicates that integrating flip teaching into students’ independent work helps them to devote more time to their homework assignments, shortens the time spent on studying the topic, enhances their motivation in learning a foreign language and improves communicative skills.